The shapes of ideas Chinese philosophy in cultural relics - Zhang, Xi (Palgrave Macmillan, an imprint of Springer Nature Singapore Pte Ltd., 2024)
"The book combines Chinese philosophy and historical knowledge and delivers the core ideas of Chinese philosophy from 72 elaborately selected pieces of cultural relics in 18 topics. Based on the structure of "Cosmology-Ontology-Theory of Mind-Nature" for ancient Chinese philosophy, the author probes the new achievements in recent years, and portrays the Chinese world of thought for its vivid transformation from pre-philosophical period to early modern period, from elitism taste to popularized orientation. By narrating the nature of being, the author brings the thought essence of ancient Chinese philosophy to the readers, meanwhile mentions the society and history, and therefore sketches the interaction among the three objects. The book elucidates the wisdom of Chinese philosophy contained in cultural relics and reveals the thought and exploration of ancient Chinese sages to the secrets of human nature." --
Keywords: Philosophy, Chinese / History; China / Antiquities